Pemaknaan Label Halal pada Kemasan Produk dan Implikasinya terhadap Perilaku Konsumsi Mahasiswa Muslim Religius - Nurlita, Naeni Indah; Farid, Nila Maulidya; Sari, Winda Kartika; Raharja, Mahardhika Cipta; Hidayat, Ma’ruf (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to explore how religious Muslim students interpret halal labels on product packaging and how these interpretations influence their consumption behavior. In the context of increasing awareness of halal product importance, halal labeling is not just a symbol of religious law, but also a guarantee of quality, safety, and trust. The research uses a descriptive qualitative method phenomenological approach, involving students from UIN Prof. K.H. Saifuddin Zuhri Purwokerto who were selected through purposive sampling. Data was collected through semi-structured interviews, literature study, and documentation, then analyzed using thematic analysis. The findings reveal that highly religious students tend to be more selective, careful, and responsible in choosing products, prioritizing those with halal certification even when priced higher. The halal label provides psychological comfort and certainty that the product aligns with Islamic principles. Additionally, a strong understanding of halal labels increases consumer loyalty and supports the growth of the halal industry through rising demand for certified products. Thus, the halal label plays a significant role in shaping the consumption patterns of religious Muslim students and contributes to the broader development of the halal industry in Indonesia.